Characterization of Hepatitis C Virus E2 Glycoprotein Interaction with a Putative Cellular Receptor, CD81 - Flint, Mike (American Society for Microbiology, 1999)
A truncated soluble form of the hepatitis C virus E2 glycoprotein, E2(661), binds specifically to the surface of cells expressing human CD81 (hCD81) but not other members of the tetraspanin family (CD9, CD63, and CD151). No differences were noted between the level of E2(661) binding to hCD81 expressed on the surface of rat RBL or KM3 cells compared to Daudi and Molt-4 cells, suggesting that additional human-cell-specific factors are not required for the primary interaction of E2 with the cell surface. E2 did not interact with African green monkey (AGM) CD81 on the surface of COS cells, which differs from the hCD81 sequence at four residues within the second extracellular region (EC2) (amino acids [aa] 163, 186, 188, and 196), suggesting that one or more of these residues defines the site of interaction with E2. Various recombinant forms of CD81 EC2 show differences in the ability to bind E2, suggesting that CD81 conformation is important for E2 recognition. Regions of E2 involved in the CD81 interaction were analyzed, and our data suggest that the binding site is of a conformational nature involving aa 480 to 493 and 544 to 551 within the E2 glycoprotein. Finally, we demonstrate that ligation of CD81 by E2(661) induced aggregation of lymphoid cells and inhibited B-cell proliferation, demonstrating that E2 interaction with CD81 can modulate cell function.